The Effect of Acetic Acid Solution Application on Duck Eggs Shell Strength and Incubation Duration During the Critical Hatching Period - Akbar Satria Bahari (Journal of Tropical Animal Science and Technology, 2026)
This study aimed to investigate the effect of different levels of acetic acid solution application on duck eggs on eggshell strength and hatching time. The materials used in this study were 180 hatching duck eggs (1–7 days old, weighing 65–75 g) from 16–18week old parent ducks. An experimental method with a Completely Randomized Design (CRD) was employed as the research design. The study consisted of three acetic acid treatment groups (P0: 0%, P1: 10%, P2: 20% acetic acid) and 6 replicates, with each experimental unit using 10 eggs. The variables measured in this study were eggshell strength (MPa) and egg hatching time (hours). Eggshell strength and hatching time data were analyzed using analysis of variance (ANOVA) and orthogonal contrast as a post-hoc test. The results showed the mean values of eggshell strength (MPa) for each treatment as follows: P0 (0.233 ± 0.022), P1 (0.125 ± 0.013), and P2 (0.144 ± 0.031); and hatching time (hours): P0 (650.438 ± 9.714), P1 (622.438 ± 5.519), and P2 (635.503 ± 2.182). Analysis of variance revealed a highly significant difference (P<0.01) in both variables due to the acetic acid application. Orthogonal contrast tests showed no significant difference in eggshell strength between treatments P1 and P2, while there was a highly significant difference (P<0.01) in hatching time between P1 and P2. It can be concluded that acetic acid application significantly reduces eggshell strength and accelerates the hatching of duck eggs. The treatment with a 10% acetic acid concentration demonstrated the most optimal effectiveness in accelerating hatching.